Pelleting and extrusion can ameliorate negative effects of toasting of rapeseed meal on protein digestibility in growing pigs - Salazar Villanea, Sergio (2017)
La Universidad de Costa Rica proporcionó una beca para el programa de doctorado de Sergio Salazar Villanea